A novel antagonist anti‐cMet antibody with antitumor activities targeting both ligand‐dependent and ligand‐independent c‐Met receptors. Issue 8 (4th July 2016) - Gonzalez, Alexandra; Broussas, Matthieu; Beau‐Larvor, Charlotte; Haeuw, Jean‐François; Boute, Nicolas; Robert, Alain; Champion, Thierry; Beck, Alain; Bailly, Christian; Corvaïa, Nathalie; Goetsch, Liliane
Abstract : c‐Met is a prototypic member of a sub‐family of RTKs. Inappropriate c‐Met activation plays a crucial role in tumor formation, proliferation and metastasis. Using a key c‐Met dimerization assay, a set of 12 murine whole IgG1 monoclonal antibodies was selected and a lead candidate, m224G11, was humanized by CDR‐grafting and engineered to generate a divalent full antagonist humanized IgG1 antibody, hz224G11. Neither m224G11 nor hz224G11 bind to the murine c‐Met receptor. Their antitumor activity was investigated in vitro in a set of experiments consistent with the reported pleiotropic effects mediated by c‐Met and, in vivo, using several human tumor xenograft models. Both m224G11 and hz224G11 exhibited nanomolar affinities for the receptor and inhibited HGF binding, c‐Met phosphorylation, and receptor dimerization in a similar fashion, resulting in a profound inhibition of all c‐Met functions in vitro . These effects were presumably responsible for the inhibition of c‐Met's major functions including cell proliferation, migration, invasion scattering, morphogenesis and angiogenesis. In addition to these in vitro properties, hz224G11 dramatically inhibits the growth of autocrine, partially autophosphorylated and c‐Met amplified cell lines in vivo . Pharmacological studies performed on Hs746T gastric cancer xenografts demonstrate that hz224G11 strongly downregulates c‐Met expression and phosphorylation. It also decreases the tumor mitotic index (Ki67) and induces apoptosis. Taken together, the in vitro and in vivo data suggest that hz224G11 is a promising candidate for the treatment of tumors. This antibody, now known as ABT‐700 and currently in Phase I clinical trials, may provide a novel therapeutic approach to c‐Met‐expressing cancers. Abstract : What's new? The c‐Met pathway is frequently deregulated in a wide range of human malignancies and its over‐expression plays a key role in tumor development and metastasis. Inhibiting c‐Met signaling is emerging as a promising strategy and several inhibitors are now at various stages of clinical development. This study describes the generation of a humanized anti‐cMet antibody that is able to inhibit both ligand‐dependent and ligand‐independent tumor growth in a sustainable fashion. This is the only full antagonist IgG1 antibody reported to date with both blocking activities and antibody‐dependent cell‐mediated cytotoxicity functions, making it arguably the best molecule in its class.